Advances in Biodegradable Electronic Skin: Material Progress and Recent Applications in Sensing, Robotics, and Human–Machine Interfaces. Issue 4 (30th November 2022) - Zarei, Mohammad; Lee, Giwon; Lee, Seung Goo; Cho, Kilwon
Abstract: The rapid growth of the electronics industry and proliferation of electronic materials and telecommunications technologies has led to the release of a massive amount of untreated electronic waste (e‐waste) into the environment. Consequently, catastrophic environmental damage at the microbiome level and serious human health diseases threaten the natural fate of the planet. Currently, the demand for wearable electronics for applications in personalized medicine, electronic skins (e‐skins), and health monitoring is substantial and growing. Therefore, "green" characteristics such as biodegradability, self‐healing, and biocompatibility ensure the future application of wearable electronics and e‐skins in biomedical engineering and bioanalytical sciences. Leveraging the biodegradability, sustainability, and biocompatibility of natural materials will dramatically influence the fabrication of environmentally friendly e‐skins and wearable electronics. Here, the molecular and structural characteristics of biological skins and artificial e‐skins are discussed. The focus then turns to the biodegradable materials, including natural and synthetic‐polymer‐based materials, and their recent applications in the development of biodegradable e‐skin in wearable sensors, robotics, and human–machine interfaces (HMIs). Finally, the main challenges and outlook regarding the preparation and application of biodegradable e‐skins are critically discussed in a near‐future scenario, which is expected to lead to the next generation of biodegradable e‐skins. Abstract : Developments of biodegradable electronic skins (e‐skins) have attracted considerable attention for successful application in wearable biosensors, artificial intelligence, physiological signal monitoring, robotics, and prosthetics. Progress in materials and various strategies for performance improvement of biodegradable e‐skins and flexible electronics are comprehensively described. The most recent research advances, current challenges, and future perspectives are also outlined and extrapolated to future applications.